Serum Exosomes MicroRNAs Are Novel Non-Invasive Biomarkers of Intrahepatic Cholestasis of Pregnancy - Dong, Ruirui; Ye, Ningzhen; Wang, Jing; Zhao, Shaojie; Wang, Tiejun; Wang, Gaoying; Shi, Xinrui; Cheng, Jing; Zhang, Yan; Yao, Tingting; Chen, Minjian; Zhang, Ting; et al. (Frontiers in Endocrinology, 2022)
Background: Intrahepatic cholestasis of pregnancy (ICP) is closely related to the occurrence of adverse outcomes. Currently, total bile acids (TBAs) are the only diagnostic index for ICP, and its sensitivity and specificity have certain limitations. In this study, we aimed to develop potential biomarkers for the diagnosis of ICP. Methods: 60 pregnant women diagnosed with ICP and 48 healthy pregnant controls were enrolled in this study. We used the Agilent miRNA array followed by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) assays to identify and validate the serum exosomes miRNA profiles in ICP and healthy pregnant controls. We employed bioinformatics to identify metabolic processes associated with differentially expressed serum exosomes miRNAs. Results: The expression levels of hsa-miR-4271, hsa-miR-1275 and hsa-miR-6891-5p in maternal serum exosomes were significantly lower in ICP patients compared to controls; the diagnostic accuracy of hsa-miR-4271, hsa-miR-1275 and hsa-miR-6891-5p was evaluated with the areas under the receiver operating characteristic curve (AUC) value of 0.861, 0.886 and 0.838, respectively. Multiple logistic regression analysis showed that a combination of the levels of hsa-miR-4271and hsa-miR-1275 afforded a significantly higher AUC (0.982). The non-error rate of a combination of all three exosomes miRNAs was the highest (95%), thus more reliable diagnosing ICP. The expression levels of all three exosomes miRNAs were negatively associated with TBAs. Furthermore, according to bioinformatics analysis, the three exosomes miRNAs were related to lipid metabolism, apoptosis, oxidative stress, and the MAPK signaling pathway. Conclusions: This study may identify the novel noninvasive biomarkers for ICP and provided new insights into the important role of the exosomes miRNAs regulation in ICP.